Escenarios e innovaciones en el sistema agroindustrial de la provincia de Entre Ríos: aportes desde un enfoque multinivel - Valentinuz, Oscar (2024)
A sustainable future requires harmonizing productive, environmental, and social aspects. This study aims to analyze the main technological and social innovation challenges faced by primary production in an agricultural province of Argentina (Entre Ríos) through a multi-level approach and prospective scenarios. Building on a prior future study that generated narratives of five archetypal scenarios for the provincial agri-food system by 2030, the "transformation" scenario (termed "metamorphosis") was selected, and the required innovations at different levels of the multi-level approach (niche, regime, and landscape) were described to bridge the gap between this desirable scenario and the continuity scenario, i.e. business as usual. Sustainable intensification, digital agriculture, and the diversification of primary production were identified as key innovations for a transition toward the desired scenario, in which state regulations and incentives at the niche and landscape levels also appear essential for advancing along a transitional path.